2018
DOI: 10.7150/jca.27368
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Ipilimumab plus Chemotherapy for Advanced Lung Cancer: A Systematic Review and Meta-Analysis

Abstract: Lung cancer is the leading cause of cancer-related deaths worldwide, with poor prognosis in advanced lung cancer patients. Platinum-based chemotherapy has always been a first-line treatment for the majority of advanced lung cancer patients, but its long-term survival benefit is limited. Ipilimumab is an immune drug that targets the CTLA-4 protein in T cells. Therefore, we evaluated the efficacy and safety of adding ipilimumab to simple chemotherapy for patients with advanced lung cancer. We searched literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
0
8
0
1
Order By: Relevance
“…Late-stage diagnosis and the limitations of classical therapies lead to a poor OS. Recent evidence suggests that immunotherapy is a powerful tool for lung cancer treatment (4)(5)(6). Therefore, the identification of novel biomarkers and promising immune-related therapeutic targets for lung cancer has become imperative in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Late-stage diagnosis and the limitations of classical therapies lead to a poor OS. Recent evidence suggests that immunotherapy is a powerful tool for lung cancer treatment (4)(5)(6). Therefore, the identification of novel biomarkers and promising immune-related therapeutic targets for lung cancer has become imperative in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…In the exploratory analysis of phase II clinical trials of combined chemotherapy using ipilimumab, 13 it was found that patients with a high expression of antibodies before treatment may benefit from this regimen. A meta-analysis 14 indicated that ipilimumab improved the PFS (six months: RR=1.16, P=0.02; one year: RR=1.39, P=0.02) and six-month immunerelated PFS (irPFS) (RR=1.60, P=0.004) in 1084 SCLC patients. However, because of the addition of ipilimumab, immune-related toxicity was more obvious in the immunochemotherapy group.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggest that immunotherapy is a sharp sword for cancers, especially for lung cancer. 3 Previous studies showed that LUAD tends to have several gene mutations, which includes TP53, KRAS, EGFR, BRAF, and ALK. [4][5][6] The somatic mutations in LUAD are well-studied and there are many targeted therapeutic strategies toward these mutations.…”
Section: Introductionmentioning
confidence: 99%